THE PRESIDENT OF ROMANIA: DESIGNATION, ROLE, MANDATE - ADELIN UNGUREANU (Annals of the University of Petrosani: Economics)
The President of Romania is elected through universal, equal, direct, secret, and freely expressed vote. In order to run for this office, the individual must be a Romanian citizen and at least 35 years of age. The election of the President is validated by the Constitutional Court of Romania, and the mandate commences upon the taking of the Oath of Office. The current duration of the presidential mandate is five years, with the same individual being entitled to a maximum of two consecutive terms. The President of Romania’s duties are generally consistent with those of a semi-presidential republic. During their mandate, the President is not allowed to belong to any political party. Among other responsibilities, the President of Romania also serves as the Supreme Commander of the Armed Forces.